Physicochemical properties of powdered protein hydrolysate from yellowstripe scad (Selaroides leptolepis) fish - Hau, Eng Huan; Mohd Zin, Zamzahaila; Nasution, Zuraidah; Shaharudin, N. A.; Mohd Zainol, Mohamad Khairi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Yellowstripe scad fish (YSF) or Selaroides leptolepis belongs to the small pelagic group that is abundantly found in South China Sea and is categorised as low value fishes. This study is designed to explore the physicochemical properties of YSF protein hydrolysate extracted using sodium phosphate buffer followed by 0.5%-2.0% of Alcalase at a series of hydrolysis time (1 hr and 2 hr). The properties of freeze and spray dried protein hydrolysate were evaluated for yield, degree of hydrolysis, protein content, microstructure and water holding capacity. Results showed that prolonged hydrolysis time exhibited increasing yield (0.6%-1.6% for spray drying and 12-16% for freeze drying) and high degree of hydrolysis (80-95%). Protein content recovered from hydrolysis process is within 20-29%. Microstructure of freeze dried YSF protein hydrolysate had 'collapsed-building' structure (irregular shapes with edges) while spray dried had small and spherical structure. Freeze dried protein hydrolysates were significantly (p < 0.05) higher than spray dried hydrolysates in water holding capacity.